Transformations of trade unionism: Comparative and transnational perspectives on workers organizing in Europe and the United States, eighteenth to twenty-first centuries - Ad Knotter (Amsterdam University Press, 2018)
The introduction explores the main theoretical positions taken in this book. Contrary to twentieth-century neoliberal or nineteenth-century wage fund theories, it starts from the assumption that trade unions are a necessary and integral part of the functioning of labour markets in societies based on wage labour. The case studies all depart from the concept of labour market control as the basic goal of union behaviour. As trade unions are "the necessary instrumentability" (J.S. Mill) of wage labour markets, it is to be expected that they will arise whenever such a market is formed. This does not mean that through time workers organized uniformly, or that there was a continuous evolution from one form of trade unionism to another. A central argument in this book is that the regulatory function of trade unions was linked to and to a great extent determined by the way production was organized. In the three centuries covered in this book, labour relations changed fundamentally, and this was reflected in different forms of trade unionism. The chapters highlight the varieties and transformations of trade unionism from a comparative and transnational perspective. They all start from Dutch examples, or incorporate a Dutch element, but the comparative and transnational approach connects these histories to general developments in Europe and the United States (the original heartlands of trade unionism) from the eighteenth century to the twenty-first.
Keywords: 330; trade unionism; labour market control; labour regimes; industrial relations; transnationalism; internationalism